Supply chain management: A system dynamics approach to improve visibility and performance - Chan, Kah Wai; Chooi, Leng Ang (UUM Press, 2011)
Competitiveness is one of the factors successful organizations excel in, and they will do anything necessary to gain an edge over their competitors.The system dynamics approach to simulation modelling is being considered as one of the methods to increase competitiveness.System dynamics is essentially a methodology suited to studying and managing complex feedback systems and provides a means for understanding the causes of industry behaviour.This research builds a complete system dynamics model for internal supply chain events (from order to ship-out) from the perspectives of a semiconductor company.System dynamics models are simulation-based models that allow the investigation and identifi cation of discrepancies between the business policy and the actual practice of key events as well as provide a better visibility of the company’s system. With the understanding of the internal workings of the supply chain system, experiments with the simulation model could provide alternative configurations to achieve better performance. This research utilizes system dynamics to better understand the supply chain system and with it, to find better solutions through experimentations with a few key variables in the supply chain system.The result of this research reveals that the company could achieve 25% reduction in inventory cost should the recommendations be followed.